Independent Entrepreneurship Training in the Digital Era for Communities in Yogyakarta - Isnawati, Isnawati; Rahmasari, Dewi; Adiansyah, Adi; Solihat, Asri; Nugraha, Sukma; Maulani, Galih Abdul Fatah; Hamdani, Nizar Alam (Indonesian Journal of Community Empowerment (IJCE), 2024)
The limited access to technology-based entrepreneurship training and the lack of practical mentoring present real obstacles for communities competing amidst the digital transformation. The primary problem lies in the inadequate understanding and skills needed to optimally utilize digital technology for business activities. The training method used included an opening session, a question-and-answer session, the implementation of the activity, and a closing session. The results of this community service activity identified that providing independent entrepreneurship training in the digital era provides a relevant contribution in encouraging the community to develop a deeper understanding of the integration of independent entrepreneurship into the context of everyday life. This training provides the community in Yogyakarta with a deeper understanding of independent entrepreneurship as a means of improving their entrepreneurial skills.